Trapped in The Digital Wave: The Role of Emotional and Social Loneliness on FoMO in Adolescent TikTok Users in East Java - Jati, Ni Made Karinadevi Permata; Sukamto, Monique Elizabeth (Journal of Educational, Health and Community Psychology, 2025)
This study examined the role of emotional and social loneliness in the fear of missing out (FoMO) among adolescent TikTok users in East Java. With the increasing use of social media among teenagers, FoMO has become a common issue linked to anxiety and discomfort over missing online interactions. A total of 205 adolescents aged 13–18 participated through a survey, using the Fear of Missing Out Scale (FoMOS) and the De Jong Gierveld Loneliness Scale (DJGLS), analyzed with linear regression. The research findings revealed that emotional and social loneliness significantly predicted increased FoMO. The novelty of this study lies in exploring the role of two dimensions of loneliness on FoMO in Indonesian adolescents. These results highlight the importance of interventions to reduce loneliness, such as strengthening peer relationships and promoting healthier social media use. Practically, the findings suggest that schools or parents should foster supportive environments and encourage balanced online–offline interactions to help mitigate FoMO and protect adolescents’ mental well-being.